Nomads the wanderers who shaped our world - Sattin, Anthony 1956- (W.W. Norton & Company, Inc., 2022)
"The remarkable story of how nomads have fostered and refreshed civilization throughout our history. Moving across millennia, Nomads explores the transformative and often bloody relationship between settled and mobile societies. Often overlooked in history, the story of the umbilical connections between these two very different ways of living presents a radical new view of human civilization. From the Neolithic revolution to the twenty-first century via the rise and fall of the Roman Empire, the great nomadic empires of the Arabs and Mongols, the Mughals and the development of the Silk Road, nomads have been a perpetual counterbalance to the empires created by the power of human cities. Exploring the evolutionary biology and psychology of restlessness that makes us human, Anthony Sattin's sweeping history charts the power of nomadism from before the Bible to its decline in the present day. Connecting us to mythology and the records of antiquity, Nomads explains why we leave home, and why we like to return again. This is the history of civilization as told through its outsiders"--